PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK - Maria Christina Sri Sunarsih (Jurnal Pendidikan Dasar, 2019)
Abstract: The purpose of this study is to describe the implementation of learning using NHT type cooperative learning models to improve the learning outcomes of thematic learning of healthy food themes. This study uses a class action research design (CAR), which was carried out in two cycles, namely cycle I and cycle II. The data collection techniques used were observation and tests. The collected data was analyzed using qualitative and quantitative descriptive analysis techniques. The results showed that learning by applying the cooperative learning model numbered head together type progressed well as indicated by the value of the implementation of learning in the first cycle to reach 77.50 and in the second cycle to get a value of 80.66. The application of cooperative learning model type Numbered Head Together (NHT) can improve student thematic learning outcomes. Classical completeness in the first cycle obtained 77.50% and the second cycle was 80.66%. Based on the results of the research with the cooperative method of the NHT model can positively influence the improvement of learning outcomes of the V-b class of SDN Dukuh Menanggal I / 424 Surabaya in the academic year 2019-2020, and this learning model can be used as an alternative thematic learning.Keywords: Tematik Learning, Cooperative Numbered Head Together Model.